The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/14644193221090868
|View full text |Cite
|
Sign up to set email alerts
|

Study on the integrated structure/control design method of magnetorheological damper for improving vehicle posture

Abstract: In order to achieve a good match between magnetorheological (MR) damper and vehicle Noise Vibration and Harshness (NVH) quality and improve vehicle posture while driving, an integrated design method of MR damper structure/control for vehicle vibration suppression was proposed considering the coupling effect between MR damper structure parameters and controller parameters. A controller was designed to control the damping force generated by the tapered channel MR damper. Furthermore, the damping force expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A tapered flow mode MR damper was designed for a certain passenger car, as shown in Figure 1 (Deng et al, 2022a). The materials of the inner and outer magnetic cores of the MR damper are both DT4, and a tapered damping channel is formed between the inner and outer magnetic cores.…”
Section: Dynamic Modeling Of Mr Dampermentioning
confidence: 99%
See 1 more Smart Citation
“…A tapered flow mode MR damper was designed for a certain passenger car, as shown in Figure 1 (Deng et al, 2022a). The materials of the inner and outer magnetic cores of the MR damper are both DT4, and a tapered damping channel is formed between the inner and outer magnetic cores.…”
Section: Dynamic Modeling Of Mr Dampermentioning
confidence: 99%
“…The research object of this paper is the roll angle of the vehicle, so the fuzzy PID controller is designed to reduce the roll of the vehicle under the conditions of double line shift test, fishhook steering test, and steering wheel angle step test (Deng et al, 2022a). The The vehicle dynamics model based on simulation can provide different steering wheel angle input.…”
Section: Vehicle Modeling and Simulationmentioning
confidence: 99%
“…Therefore, the MR valvecontrolled damper is widely used in suspension systems [3]. The pressure drop at the valve inlet and outlet can be accurately controlled by changing operating currents, thereby adjusting the dynamic damping force [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Rashid, M. M [27] designed a hybrid fuzzy controller based on quarter suspension, and demonstrated through experiments that the designed hybrid fuzzy controller can effectively suppress random road disturbances and improve the smoothness of the vehicle. Deng, Z [28] designed a fuzzy PID control controller with the vehicle's vertical and pitch acceleration as the control target for the vibration reduction requirements of the vehicle magneto-rheological suspension system, and the simulation demonstrated that the designed controller can effectively improve the vehicle attitude. From the above studies, it can be observed that MRD devices and fuzzy PI control algorithms are now widely used in the field of intelligent vibration damping.…”
Section: Introductionmentioning
confidence: 99%